The baptismal episode as trinitarian narrative: proto-trinitarian structures in Mark's conception of God - Mortensen, Hallur (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
Cover -- Title -- Acknowledgements -- Table of Contents -- List of Abbreviations -- Introduction: Mark's God in the History of Recent Research -- I. Nils A. Dahl's Plea and the Earliest Responses -- a. Nils A. Dahl (1975) -- b. Robert C. Tannehill (1979) -- c. John R. Donahue (1982, 1984) -- II. Early German Contributions -- a. Joachim Gnilka (1992) -- b. François Vouga (1995) -- c. Klaus Scholtissek (1996) -- III. Recent Contributions -- a. Paul L. Danove (2001, 2005) -- b. Jack Dean Kingsbury (2002) -- c. Gudrun Guttenberger (2004) -- d. Geert van Oyen (2006, 2012)